2009
DOI: 10.3238/arztebl.2009.0003
|View full text |Cite
|
Sign up to set email alerts
|

AGnES

Abstract: Structural redundancy is avoided by directly placing the AGnES employees in the general practitioners' practices. Based on the results of the AGnES projects, the law in Germany has now been amended to enable implementation of the AGnES project in the regular health care system from January 2009 onward. The next steps to be taken are the establishment of adequate reimbursement within the catalog of the statutory health insurance scheme and a detailed definition of the required qualifications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
3

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 3 publications
0
18
0
3
Order By: Relevance
“…All participating GPs found that the quality of care within the AGnES-concept was comparable to usual care for the majority of the participating patients [5]. …”
Section: Introductionmentioning
confidence: 99%
“…All participating GPs found that the quality of care within the AGnES-concept was comparable to usual care for the majority of the participating patients [5]. …”
Section: Introductionmentioning
confidence: 99%
“…We examined this question for the AGnES Brandenburg project which was conducted in the ambulatory healthcare centre with six GP-practices [10]. …”
Section: Resultsmentioning
confidence: 99%
“…To examine the option of delegating GP-home visits, we developed and implemented the AGnES concept (AGnES = GP-supporting, community-based, e-health-assisted, systemic intervention) [10,11]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Ableitung der evozierten Potenziale kann unter Anleitung durch eine geschulte medizinisch-technische Angestellte oder sogar durch eine gut geschulte Krankenschwester durchgeführt werden[1]. Die Befunde können über sichere Datenleitungen in Echtzeit transferiert werden, ein erfahrener Neurologe kann die Ableitungen interpretieren und den Befund erstellen[6].Abb.…”
unclassified